Ingested Human Insulin Inhibits the Mosquito NF-κB-Dependent Immune Response to Plasmodium falciparum - Pakpour, Nazzy (American Society for Microbiology, 2012)
We showed previously that ingested human insulin activates the insulin/IGF-1 signaling pathway in Anopheles stephensi and increases the susceptibility of these mosquitoes to Plasmodium falciparum. In other organisms, insulin can alter immune responsiveness through regulation of NF-κB transcription factors, critical elements for innate immunity that are also central to mosquito immunity. We show here that insulin signaling decreased expression of NF-κB-regulated immune genes in mosquito cells stimulated with either bacterial or malarial soluble products. Further, human insulin suppressed mosquito immunity through sustained phosphatidylinositol 3-kinase activation, since inhibition of this pathway led to decreased parasite development in the mosquito. Together, these data demonstrate that activation of the insulin/IGF-1 signaling pathway by ingested human insulin can alter NF-κB-dependent immunity, and ultimately the susceptibility, of mosquitoes to P. falciparum.